The Influence of Verbal Abuse and Interpersonal Communication by Parents on Children's Self-Confidence - Ghozali, Ade Ahmad; Yudha, Rivo Panji (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to determine the effect of verbal abuse and parental interpersonal communication on the self-confidence of children aged 4-5 years in Legonkulon Sub-district, Subang. Verbal abuse is identified as the use of harsh, insulting, or demeaning words by parents, while good interpersonal communication includes openness, empathy, and mutual respect. This study used a quantitative approach with survey method and multiple linear regression analysis to analyze data from 96 children. The findings showed that verbal abuse and interpersonal communication together significantly affected children's self-confidence, with verbal abuse explaining 77.7% of the variance in children's self-confidence. This study provides recommendations for appropriate interventions, such as effective communication training for parents and educational programs to raise awareness about the importance of positive communication. Thus, this study contributes to a better understanding of the factors that influence children's self-confidence and develops more effective intervention strategies. The results showed that there is an effect of verbal abuse and interpersonal communication simultaneously on children's self-confidence. The R value of 94% indicates a very strong relationship between the two independent variables (verbal abuse and interpersonal communication) with the dependent variable (children's self-confidence). The F value of 625.457 with a test significance of 0.000 indicates that the regression model used is significant and can be used to predict the effect of verbal abuse and interpersonal communication on children's self-confidence.